Symptoms and exacerbations in asthma: an apparent paradox?. (October 2019) - Morjaria, Jaymin B.; Rigby, Alan S.; Morice, Alyn H.
Background: There is a dearth of data on prospectively recorded symptoms in patients with uncontrolled asthma. Asthma symptoms and exacerbation rate are commonly thought to be associated. The aim of this study was to analyse asthma symptoms of cough, wheeze, chest tightness and breathlessness in an uncontrolled asthma cohort. We also examined the effect of maintenance and reliever therapy (MART) on these symptoms and its effect on exacerbation rate. Methods: Adults with uncontrolled asthma electronically recorded their asthma symptom severity scores twice-daily over a period of 48 weeks following randomisation to beclometasone/formoterol twice daily plus pro re nata (prn) salbutamol or MART. Subjects with symptom scores of ⩾2 (ranging from 0 to 3 for each symptom) were considered more symptomatic, whereas those below a score of 2 were considered less severe. The influence treatment on exacerbation frequency and symptom profiles were then correlated. Results: Of the 1701 subjects in the analyses, 1403 were symptomatic with ⩾100 symptom episodes for one symptom. The remaining 298 subjects were classified as pauci-symptomatic. There was poor association between the frequency and symptom severity score for each symptom. Surprisingly, wheeze was the least reported symptom. Females were more likely to be polysymptomatic. MART compared with prn salbutamol markedly attenuated severe asthma exacerbations. This effect was most notable in subjects with fewer symptoms. Conclusions: In uncontrolled asthma, there is a poor correlation between reported symptoms and exacerbation frequency. This post hoc analysis suggests that MART should not be reserved for symptomatic subjects but achieves the greatest benefit in pauci-symptomatic patients with asthma. Trial registration: ClinicalTrials.gov identifier: NCT00861926